Understanding the prescribing practices of mental health providers during pregnancy: The role of uncertainty in the patient-provider relationship - Rachel Eakley; Susan Kools; Allison Deutch; Audrey Lyndon (SSM: Qualitative Research in Health)
Rationale: Untreated mental health concerns during pregnancy can have a devastating impact on the well-being of the pregnant person and present risks to the developing fetus, birth outcomes, and child development. Despite these risks, patients report difficulty accessing or maintaining mental health treatment during pregnancy. Clinical reluctance among outpatient psychiatric mental health providers to provide medication management to pregnant patients has been proposed as a significant barrier to care, however, little is known regarding what creates and maintains this reluctance among providers. Objective: Explore outpatient psychiatric mental health providers’ beliefs, experiences, and treatment decisions with an emphasis on understanding reluctance to treat mental health concerns during pregnancy. Method: Using constructivist grounded theory, we conducted in-depth interviews with 21 outpatient psychiatric mental health providers, including psychiatric mental health nurse practitioners and psychiatrists who practiced with adult patients in the United States. Interviews were audio recorded and transcribed verbatim for analysis using dimensional and situational analysis techniques. Results: A lack of training, inadequate knowledge, and fear of personal consequences were frequently cited as motivating factors behind this reluctance. Providers often felt unprepared to treat pregnant clients and appeared to make treatment decisions to protect themselves from perceived legal consequences or to mitigate their own anxiety/discomfort rather than guided by evidence-based guidelines or patient interests. Conclusion: Many providers endorsed discomfort treating pregnant patients and observed this reluctance among peers and colleagues. The processes used to avoid discomfort and uncertainty may limit treatment opportunities for pregnant people in need of mental health care. The results of this study provide implications for education and clinical practice that may lead to improved access to mental health care among pregnant people.